Young Adults' Inferences Surrounding an Alleged Sexual Assault: Alcohol Consumption, Gender, Dress, and Appearance Schematicity. (April 2016) - Johnson, Kim K. P.; Ju, Hae Won; Wu, Juanjuan
A 2 (dress) × 2 (victim alcohol use) × 2 (perpetrator alcohol use) between subjects factorial design was used to investigate the influence of dress, alcohol use, and gender of participants on inferences made by college students ( N = 430) about an alleged victim and perpetrator of a sexual assault. Whether being schematic on appearance moderated the influence of dress was also tested. Dress of the victim and alcohol use significantly influenced inferences of the alleged victim and the perpetrator. There was an interaction effect for dress, alcohol use, and gender on inferences concerning the perpetrator. Wearing body-revealing dress and alcohol use by the alleged victim were interpreted as a sign of the sexual interest of the victim. Alcohol use by the alleged perpetrator influenced inferences concerning the believability of his statements. Being schematic on appearance did not appear to moderate the influence of dress on participants' perceptions.